The future engineer: sustainability and the new material world - Maleque, Md. Abdul; Ahmad Azhar, Ahmad Zahirani; Efeoğlu, İhsan (ACA Publishing, 2025)
This keynote presents a comprehensive outlook on the advancing role of engineering in a rapidly changing global scenery. It starts by reflecting on the past of engineering, where the discipline primarily contributed to the mechanics of materials, infrastructure development, and materials strength, focusing on performance, efficiency, and cost optimization. These foundations established the technical rigour upon which modern engineering continues to build. The talk then moves to the present state of engineering, characterized by rapid digitalisation, automation, and increasing societal expectations. Today’s engineers operate in complex, interconnected systems where environmental constraints, resource limitations, and resilience requirements demand solutions that extend beyond traditional engineering practices. Looking toward the future, the presentation predicts that engineers will be integrators of technology, system thinking, and ethical responsibility. Future engineering practice will require adaptability, interdisciplinary collaboration, and the ability to anticipate long-term societal and environmental impacts rather than responding only to immediate technical challenges. Central to this future is the emergence of a new material world, where advanced materials—such as smart, bio-derived, and circular-economy materials—serve as key enablers of sustainable innovation. Materials are positioned not merely as structural components but as active, multifunctional systems that shape the performance, durability, and environmental footprint of engineered solutions. The presentation then explores the transformative role of artificial intelligence and data-driven engineering, highlighting how AI accelerates materials discovery, enhances performance prediction, optimizes processing parameters, and supports advanced characterization. This shift from trial-and-error experimentation to predictive design fundamentally changes how engineers innovate and make decisions. Building on these technological advances, the presentation emphasizes sustainability as a core engineering necessity. Engineers must adopt lifecycle thinking, integrate circular-economy principles, reduce carbon footprints, and design regenerative systems that balance technological progress with environmental stewardship. Finally, the presentation highlights the importance of ethics in engineering practice. As engineering solutions grow more powerful and influential, ethical responsibility, social accountability, and environmental justice must guide decision-making. The future engineer is thus expected to abide by ethics with environmental stewardship, social responsibility and professional integrity.